Incomplete Ear Amputation. Issue 8 (November 2018) - Zhang, Chao; Teng, Li; Xu, Jia-Jie; Lu, Jian-Jian; Xie, Fang; Yang, Li-Ya; Li, Shu-Yuan; Wu, Huan-Huan; Sun, Heng; Yang, Biao
Abstract : Abstract: Ear amputations are common in emergency departments as the auricle's protrusion from the lateral aspect of the head makes it particularly susceptible to trauma. Of the numerous approaches for auricle injuries, the classic methods include microsurgical replantation, primary reattachment, composite graft, retroauricular pocket principle, 1 secondary reconstruction with rib cartilage, and methods using postauricular flap. The success of the operation depends largely on choosing the appropriate surgical procedure since many factors can influence surgical outcome. There is no 1 gold standard technique to treat the variety of auricle injuries. Inappropriate choice of surgical approach can be detrimental to subsequent reconstructive surgery. Therefore, the initial choice of optimal surgical approach is particularly important. In this article, a rare report of left subtotal ear laceration with inferior lobule pedicle by nonmicrosurgical primary reattachment was presented. The operation obtained an ideal cosmetic effect.